Evaluation of novel molecular markers for monitoring drug resistence in Plasmodium falciparum malaria - Henriques, Gisela Cristina Lourenço (2011)
Tese de mestrado, Microbiologia Clínica, Faculdade de Medicina, Universidade de Lisboa, 2010